(untitled) (Konferensiyalar | Conferences, 2024)
This article is dedicated to examining the use of distance learning methods in contemporary teaching. The author examines the major challenges facing teachers in the face of exclusion and offers solutions. Topics include adapting new technologies, engaging with students, personalized learning, and tracking progress. Distance education development is considered an integral part of the modern educational landscape.